Pluralitas Agama dan Faham Keagamaan: Pelajaran Dari Pondok Pesantren Nurul Jadid - Mursyid, Mursyid (Universitas Nurul Jadid, 2018)
This article attempts to provide a sociological perspective on the religious pluralism and ideology, and its implementation in the leadership system of Nurul Jadid islamic boardingschool at Probolinggo, East Java. Additionally, it also aims to argue the ways cultural power and negotiation are implemented by leaders of pesantren in building plural education for santri. To deeply analyze it, it is important first to describe the common pattern of Muslim in perceiving the diversity of religions and religious ideologies in Islam. One of the ways Nurul Jadid has carried out is to strenghten cultural roots of pesantren and to adapt it with social actions under kiai’s modelling figure, since the kiai and pesantren tradition are two ornaments contributing on the formation of santri’s behaviors.Keywords: Religious Plurality, Religious Ideologies, Pesantren Nurul Jadid